Experimental Investigation of a Cyclic Duopoly Game - Sebastian J. Goerg; Reinhard Selten (University of Bonn, Bonn Graduate School of Economics (BGSE), 2007)
The notion of a cyclic game has been introduced by Selten and Wooders (2001). They illustrate the concept by the analysis of a cyclic duopoly game. The experiments reported concern this game. The game was played by eleven matching groups of six players each. The observed choice fre- quencies were compared with the predictions of Nash equilibrium, impulse balance equilibrium (Selten, Abbink and Cox (2005), Selten and Chmura (2007)) and two-sample equilbrium (Osborne and Rubinstein(1998)). Pair- wise comparisons by the Wilcoxon Signed-rank test show that impulse balance equilibrium as well as two-sample equilibrium have a significantly better predictive success than Nash equilibrium. The difference between impulse balance equilibrium and two-sample equilibrium is not significant.In each matching group three players acted only in uneven periods and the other three only in even periods. This game has two pure strategy equi- libria in which both types of players behave differently. The data exhibit a weak but significant tendency in the direction of coordination at a pure strategy equilibrium.
Keywords: C90; D43; C73; 330; cyclic game duopoly experiment; impulse balance equilibrium; two-sample equilibrium; Dynamisches Spiel; Duopol; Experiment; Gleichgewicht; Theorie